2005
DOI: 10.1063/1.1849416
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the carrot defect in 4H-SiC epitaxial layers

Abstract: Transmission electron microscopy and KOH etching were used to determine the structure of the carrot defect in 4H-SiC epilayers. The defect consists of two intersecting planar faults on prismatic {11¯00} and basal {0001} planes. Both faults are connected by a stair-rod dislocation with Burgers vector 1∕n [101¯0] with n>3 at the crossover. A Frank-partial dislocation with b=1∕12[44¯03] terminates the basal fault.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 16 publications
3
55
0
Order By: Relevance
“…Benamara et al developed a geometrical model of a carrot defect consisting of a basal plane fault and a prismatic fault with a stair-rod dislocation at the crossover [4]. They also found that carrot defects are connected with a threading dislocation in the substrate [27].…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Benamara et al developed a geometrical model of a carrot defect consisting of a basal plane fault and a prismatic fault with a stair-rod dislocation at the crossover [4]. They also found that carrot defects are connected with a threading dislocation in the substrate [27].…”
Section: Methodsmentioning
confidence: 96%
“…Defect densities in typical off-angled 4H-SiC epilayers can be 10 2 -10 4 cm -2 for threading screw dislocations (TSDs) with Burgers vector of 1c[0001], 10 3 -10 5 cm -2 for threading edge dislocations (TEDs) with Burgers vector of 1/3〈1120〉 type and 10 0 -10 3 cm -2 for basal plane dislocations (BPDs) with Burgers vector of 1/3〈1120〉 type [2,3]. Other types of extended defects, such as carrot defects [4,5], basal plane Frank-type defects [6], 3C inclusions [7][8][9][10] and 8H stacking faults [11,12], may also be present in 4H-SiC epilayers. The impact of extended defects on the electrical characteristics of devices may vary depending on the defect structure.…”
mentioning
confidence: 99%
“…Similar calculation is applicable in case of the carrot defects observed on 8 off cut substrates. 34 In order to get insight in the structure of the triangular defects, LTPL and Raman measurements were carried out on the defect area within the triangles. The LTPL spectra showed none, or in some cases, strongly diminished luminescence of the usual near-band gap emission of the 4H-SiC polytype, with no detectable contribution from other polytypes.…”
Section: F Characterization Of the Triangular Defectsmentioning
confidence: 99%
“…Although named differently from group to group, three types of stacking faults according to their fault vectors have been reported: Shockley fault with fault vector of a/3 h1 " 100i type, [2][3][4] Frank fault with fault vector of (c/2) [0001] or (c/4) [0001], 5 and those comprising some kind of combination of the previous two. [6][7][8][9][10] Among these faults, Shockley faults have been shown to be associated with the degradation of power devices, as the expansion of such faults in the junction area can impede current flow and, as a result, increase the on-state resistance. 3 In the epilayer, the morphology of the Shockley faults responsible for the device degradation is found to have a rhombus shape with the sides along h11 " 20i directions and angles of 60°and 120°, bounded by 30°partial dislocation loops.…”
Section: Introductionmentioning
confidence: 99%